HUBUNGAN PENGARUH IKLAN OBAT BATUK DITELEVISI TERHADAP SWAMEDIKASI OBAT BATUK PADA MASYARAKAT DI APOTEK NURSYIFA - masfah raudlotus (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2022)
ABSTRACT Advertising is a medium used to convey information through mass media, including television. One of them is cough medicine advertisements that can influence the audience to self-medicate without being based on drug knowledge, causing medication errors. This study aims to determine the relationship between the influence of cough medicine advertisements on television on cough medicine self-medication in the community at the Nursyifa Pharmacy in March 2021. This research was carried out using observational analysis. The sampling method was carried out using random sampling method, obtained as many as 100 respondents. The results showed that the acquisition by age at the age of 17-25 years was 48%. Based on gender, women were 56%. Based on education, at the SMA/SMK level as much as 65%. In the Chi-Square analysis obtained a significant value (p value) 0.840 where the p value> 0.05 and the calculated r value (0.0407) < r table (3.841) it can be concluded that